AN OVERVIEW OF WIRE ELECTRODE VIBRATIONS ON WEDM (Nonconventional Technologies Review, 2015)
The paper presents the particularities of wire electric discharge machining (WEDM) technology regarding electrode-tool vibration (wire-tool vibration). It shows how the electrode-tool vibrates, as well as the shape of thevibration. The novelty of the approach is also explained, together with an overview of the factors which impact wire electrode processing and which are essential in overcoming the natural complexity of the phenomena involved. To that extent, the presented mathematical model – which uses only slight approximations to allow its study – can successfully be used in practicalimplementations to improve the accuracy of processing through wire electric discharge machining, especially with regard to positional precision and shape of surfaces machined.
Keywords: WEDM; machining precision; wire electrode vibration; multi-discharge; mathematical model